dmrt2 and myf5 Link Early Somitogenesis to Left-Right Axis Determination in Xenopus laevis - Tingler, Melanie; Brugger, Amelie; Feistel, Kerstin; Schweickert, Axel (Frontiers in Cell and Developmental Biology, 2022)
The vertebrate left-right axis is specified during neurulation by events occurring in a transient ciliated epithelium termed left-right organizer (LRO), which is made up of two distinct cell types. In the axial midline, central LRO (cLRO) cells project motile monocilia and generate a leftward fluid flow, which represents the mechanism of symmetry breakage. This directional fluid flow is perceived by laterally positioned sensory LRO (sLRO) cells, which harbor non-motile cilia. In sLRO cells on the left side, flow-induced signaling triggers post-transcriptional repression of the multi-pathway antagonist dand5. Subsequently, the co-expressed Tgf-β growth factor Nodal1 is released from Dand5-mediated repression to induce left-sided gene expression. Interestingly, Xenopus sLRO cells have somitic fate, suggesting a connection between LR determination and somitogenesis. Here, we show that doublesex and mab3-related transcription factor 2 (Dmrt2), known to be involved in vertebrate somitogenesis, is required for LRO ciliogenesis and sLRO specification. In dmrt2 morphants, misexpression of the myogenic transcription factors tbx6 and myf5 at early gastrula stages preceded the misspecification of sLRO cells at neurula stages. myf5 morphant tadpoles also showed LR defects due to a failure of sLRO development. Gain of myf5 function reintroduced sLRO cells in dmrt2 morphants, demonstrating that paraxial patterning and somitogenesis are functionally linked to LR axis formation in Xenopus.